Effects of seed priming with chitosan solutions of different acidity on seed germination and physiological characteristics of maize seedling - SHAO Chen-xia; HU Jin; SONG Wen-jian; HU Wei-min (浙江大学学报. 农业与生命科学版)
The effects of seed priming with acidic (pH5.1) and near neutral (pH6.4) chitosan solutions on seed germination and physiological characteristics of seedling were investigated using four maize materials. The results showed that priming treatments with two acidic chitosan solutions significantly enhanced the energy of germination, reduced mean germination time and increased shoot height and chlorophyll content. There were no significant difference in germination percentage between primed new seeds of three materials and un-treated control. The germination percentage of old seeds of Chaotian No.3 was, however, lower than that of the control. The POD activity and MDA content of the shoots of Suyu No.1 and Chaotian No.3 were obviously increased and decreased respectively after priming with pH5.1 chitosan solution. The POD activity was significantly decreased, and MDA content had no significant difference in the shoots of Chaotian No.3 old-aged seeds compared to the control. Concerning the CAT activity in the shoots of the three maize materials, including old-aged seeds, there were no markedly differences between the treatments and the control. Thus, it seems that chitosan is a new promising priming material for maize seed treatment, and no significant difference was found between the two acidic chitosan solutions and both are efficient in improving vigor of maize seeds.